Effects of the pandemic on access to health services in Santiago de Cali during the period 2020 to 2021 (Revista Electrónica Calidad en la Educación Superior, 2025)
Health systems and governments around the world were not prepared to provide health care during the Covid-19 pandemic period: most countries had problems in ensuring non-communicable, high-cost and chronic diseases, in addition to the medical care of the Covid pandemic. Cali was not exempt to this problem despite the strategies implemented such as home care, teleconsultation and prioritization of vulnerable population groups.OBJECTIVE: To identify the main access barriers that affect the provision of health services in Santiago de Cali during the COVID-19 pandemic in the period 2020 to 2021.MATERIAL AND METHODS: A descriptive cross-sectional study was carried out, using the information collected by the Cali Public Health Secretariat through the Community Care Service (SAC) during the years 2020 to 2021. A total of 47,253 reports were used.RESULTS: The Aguablanca District (communes 13, 14, 15 and 21) had the highest percentage of reports of accessibility barriers with 21% and the south of the city (communes 10, 17 and 18) with 16%. The economic impact of Covid-19 increased precariousness and poverty in the city.CONCLUSIONS: The limited health infrastructure in areas such as the Aguablanca district increased disparities in health care, making access especially difficult for the most vulnerable sectors of the population.
Keywords: Barriers; access; COVID-19; care; Pandemic; Accessibility; Health